Growing up in a Family as a Time of Identity Formation - Ewa Dziewońska (Ignatianum University Press, 2018)
The article presents the problem of the identity formation of an adolescent, in the context of the most socially significant reference group - the family. Adolescence is a time for searching for answers to many questions about the sense of life, goals, values, priorities. The individual identity formation process is a unique developmental opportunity, but at the same time a difficult period for those growing up, as well as their family. The article discusses the main directional changes which accompany identity formation and presents the social context of this process. It is a parental task to create a safe space of living together for their growing children, where there are common beliefs about values, ideals and life priorities. The article especially highlights the meaning of spiritual and world-view questions, which - as a basis of parents' lives - give directions to their children's pursuit of answers to the basic questions accompanying identity formation.